2021
DOI: 10.3390/f12091161
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tree Drought Resistance and Climate-Growth Relationships under Different Tree Age Classes in a Pinus nigra Arn. ssp. salzmannii Forest

Abstract: The magnitude of drought impact in forest ecosystems depends on which group of trees are more severely affected; greater mortality of smaller trees can modulate the trajectories of succession, while the mortality of larger trees can disproportionately offset the ecosystem’s carbon balance. Several studies have documented a greater vulnerability of large trees to extreme droughts while some other studies reported a greater growth reduction in smaller trees during droughts. We tested these hypotheses by comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
1
7
1
Order By: Relevance
“…Camarero et al (2018) observed that an extreme drought induced a marked growth reduction in declining black pine individuals when accounting for age effects on growth rates (younger declining and older non-declining individuals). Nevertheless, these results are in contrast with other studies conducted both on black pine (e.g., Lucas--Borja et al, 2021;Granda et al, 2018;Martin-Benito et al, 2008) and other tree species (e.g., Bose et al, 2021;Bennett et al, 2015;Dorman et al, 2015). In these studies, older trees were found to be less resistant to drought than younger trees and the impact of drought events on growth and mortality rates in larger trees was relatively greater than in smaller trees.…”
Section: Influence Of Tree Age On Drought Responsescontrasting
confidence: 72%
“…Camarero et al (2018) observed that an extreme drought induced a marked growth reduction in declining black pine individuals when accounting for age effects on growth rates (younger declining and older non-declining individuals). Nevertheless, these results are in contrast with other studies conducted both on black pine (e.g., Lucas--Borja et al, 2021;Granda et al, 2018;Martin-Benito et al, 2008) and other tree species (e.g., Bose et al, 2021;Bennett et al, 2015;Dorman et al, 2015). In these studies, older trees were found to be less resistant to drought than younger trees and the impact of drought events on growth and mortality rates in larger trees was relatively greater than in smaller trees.…”
Section: Influence Of Tree Age On Drought Responsescontrasting
confidence: 72%
“…Tree growth responses to drought can depend on tree sizes (D'Amato et al 2013;Schwarz & Bauhus 2019) and stand characteristics (Bottero et al 2017;Bose et al 2018;Andrews et al 2020). For example, small Pinus nigra trees were more drought sensitive, in terms of growth, in mixed conifer stands in Spain (Martı ´n-Benito et al 2008), while large trees were more sensitive in mixed Picea abies and Fagus sylvatica stands in Germany (Pretzsch et al 2018), as well as in pure Pinus nigra stands in Spain (Lucas-Borja et al 2021). Several studies reported higher mortality rates of large trees under drought stress (Bennett et al 2015;Olson et al 2018), while others documented higher mortality of smaller trees (van Mantgem et al 2009;Colangelo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“… 2018 ), as well as in pure Pinus nigra stands in Spain (Lucas‐Borja et al . 2021 ). Several studies reported higher mortality rates of large trees under drought stress (Bennett et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, drought stress resistance can substantially change with the tree age. As referred by Lucas-Borja et al (2021), effect of water inbalance (precipitation minus evapotranspiration) on basal area increment was lower in younger age classes (1-39 years old) of black pine (Pinus nigra Arn. ssp.…”
Section: Discussionmentioning
confidence: 86%
“…Since conflicting results come from studies on aging effect in tree drought resistance (e.g. Li et al, 2012;Lucas-Borja et al, 2021;Unawong et al, 2022), a representative tree age seems to be an important issue in the species evaluation process. We suppose that juvenile plants, fully manifesting species differences, could meet this requirement.…”
Section: Introductionmentioning
confidence: 99%